(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study aims to investigate the factors influencing the innovative performance of police stations in Thailand by developing a linear structural equation model. The research focuses on four key factors: technological innovation, knowledge management, culture of innovation, and innovation management. The primary objective is to assess the relationships between these factors and their influence on the performance outcomes of police stations in Thailand. By examining the direct, indirect, and overall impacts of the aforementioned factors on police station performance, this study aims to contribute to academic knowledge and offer valuable insights for the field of law enforcement. The research findings reveal that all the variables in the model have a positive direct effect on the factors influencing innovation performance, indicating their significance in driving effective performance within police stations. The model explains 56% of the variance in the performance factors, highlighting the substantial influence of the studied variables. Among the factors, IT technology innovation exhibits the highest impact on organizational performance, followed by cultural innovation and knowledge management. Specifically, IT technology innovation has the highest direct effect on performance, followed by knowledge management. Furthermore, knowledge management, which is improved through innovation management, demonstrates the highest indirect influence on organizational performance. The study underscores the importance of IT technology innovation, knowledge management, and cultural innovation in enhancing the performance of police stations in Thailand. The research findings contribute to a deeper understanding of these factors, facilitating academic discussions and potential practical applications in the realm of law enforcement.